Residual Stress Distribution and Fatigue Behavior of Combined Bolted–Welded Joints - Xiaoguang Liu; Lei Jiang; Gao Cheng; Jun Liu; Banghao Xu; Ruibao Jin (Buildings)
Combined bolted–welded joints use both bolting and welding methods to connect several members, resulting in a versatile and robust solution for structural connections. However, very limited studies have focused on the residual stress distribution and fatigue behavior of these joints. In this paper, a total of eight specimens of double lap joints using bolts and fillet welds were fabricated and tested to measure the residual stress distribution. A finite element model was also developed for predicting the residual stress and residual deformation, and then it was validated against the test results. The effects of different welding parameters on the residual stress and residual deformation were evaluated, including the welding sequence (four different welding sequences) and welding process (welding speeds of 4 mm/s, 6 mm/s and 10 mm/s; welding powers of 5000 W, 6000 W and 7000 W; and post-weld heat treatments of no insulation, insulation at 200 °C and insulation at 300 °C). The fatigue behaviors of combined bolted–welded joints with and without residual stresses were compared in terms of the fatigue life of crack propagation. It was shown that the maximum residual stress was approximately 450 MPa, far exceeding the yield strength of steel plate of 335 MPa, while welding sequence 1 produced the smallest residual stresses. Due to the presence of welding residual stresses, the fatigue life of combined bolted–welded joints was reduced by nearly 40%, which indicated that the fatigue life of the joint would be overestimated without considering the residual stresses.